The spirit that gives life : - Rishel, Joseph Francis (Duquesne University Press, 1997)
It's too much like an entire semester or two's worth of a history textbook for me. As it was, it took me a few hours just to read the captions that accompanied all of the pictures. There were a lot of great pics and the captions I believe summed up very nicely the context of the text. So, cheating was okay in this case. I actually learned a lot!